Bregman Asymptotic Pointwise Nonexpansive Mappings in Banach Spaces - Chin-Tzong Pang; Eskandar Naraghirad (Abstract and Applied Analysis)
We first introduce a new class of mappings called Bregman asymptotic pointwise nonexpansive mappings and investigate the existence and the approximation of fixed points of such mappings defined on a nonempty, bounded, closed, and convex subset C of a real Banach space E. Without using the original Opial property of a Banach space E, we prove weak convergence theorems for the sequences produced by generalized Mann and Ishikawa iteration processes for Bregman asymptotic pointwise nonexpansive mappings in a reflexive Banach space E. Our results are applicable in the function spaces Lp, where 1<p<∞ is a real number.